Immunomodulatory Effects of Pulmonarom®: In Vitro Induction of TLR and Cytokine Expression in Human Dendritic Cells - Juan A. Hernández-Aceves; Sandra Georgina Solano-Gálvez; Arturo A. Wilkins-Rodríguez; José Delgado-Domínguez; Alberto Garcia Lozano; Carlos Cabello-Gutierrez; Lidia Flor Estela Huerta; Gladis Fragoso; Laila Gutiérrez-Kobeh; Rosalino Vázquez-López (Pharmaceuticals)
Background: Bacterial lysates are known to modulate the immune response against respiratory infections. However, the effects of the commercial bacterial lysate Pulmonarom® on dendritic cells—particularly human monocyte-derived dendritic cells (moDCs)—have not been studied. Additionally, limited data are available on the expression of Toll-like receptors (TLRs) and cytokines following stimulation with bacterial lysates. Methods: Human monocytes were isolated from buffy coats and differentiated into moDCs. Pulmonarom® was lyophilized, quantified, and used to stimulate moDCs. Ultrastructural changes were evaluated using transmission electron microscopy. The expression of TLRs and selected cytokines was analyzed by flow cytometry. Results: Pulmonarom® stimulation induced morphological changes in moDCs, including an increased number of dendrites and lysosomes. It also led to the upregulation of MHC class II molecules and TLRs 2, 3, 6, and 7. Additionally, the production of IL-4, IL-6, IL-8, and MCP-1 was significantly increased. Conclusions: Pulmonarom® promotes moDC maturation, characterized by enhanced antigen presentation capabilities and lysosomal activity, along with increased expression of specific TLRs and cytokines. These features suggest a trained immunity phenotype in moDCs, potentially improving their ability to initiate adaptive immune responses against respiratory pathogens. To our knowledge, this is the first study to investigate the immunomodulatory effects of Pulmonarom® on human moDCs, providing novel insights into its potential as an immunotherapeutic adjuvant.